Effect of formaldehyde-based additive against African swine fever virus in complete swine feed - V. D. Ly; T. V. Hoang; A. K. Dang; S. Aupanun; C. Wongpukdee (Journal of the Indonesian Tropical Animal Agriculture, 2022)
African swine fever (ASF) is currently considered the serious contagious disease of the swine in-dustry worldwide. The feed and feed ingredients have been recognized as a potential risk factor for Af-rican swine fever virus (ASFV) transmission. No commercial vaccines and effective drugs against ASFV are available to date. This study aimed to examine the antimicrobial SALTEC™ 512, a formal-dehyde-based additive, at an application rate of 1.0; 2.0; and 3.0 kg/t feed against ASFV in complete swine feed. The effect of SALTEC™ 512 was evaluated by a contaminated ASFV feed assay. Our study reveals that SALTEC™ 512 inactivated ASF/VN/Pig/Hue/1270 strain in complete swine feed at an inclusion rate of 1.0 kg/t feed on Day 1 post inoculation. The most effective action was noticed at an inclusion level of 3.0 kg/t feed on Day 7 post inoculation. The antiviral activity of SALTEC™ 512 against ASF/VN/Pig/Hue/1270 was dose and time-dependent. Overall, SALTEC™ 512 may be a po-tential additive to reduce the risk of ASFV transmission via feed contamination.